Effects of greenwashing on financial performance: Moderation through local environmental regulation and media coverage - Li, Wei; Li, Weining; Seppänen, Veikko; Koivumäki, Timo (Business strategy and the environment, 2023)
Recent research suggests that the effect of greenwashing and corporate financial performance (CFP) is ambiguous. This call for study the contextual factors that create contingencies in the greenwashing–CFP relationship. Using a sample of 2816 observations covering 735 Chinese‐listed firms in 21 different industries from 2013 to 2017, this research examines the effect of greenwashing on CFP and explores the moderating effects of local environmental regulation, media visibility and media favourability. Results show that greenwashing positively affects CFP and effect weakened with stringent environmental regulations and reversed with low media favourability. Our finding implies that stakeholders could hardly identify greenwashing in the context of an emerging economy with high‐level information asymmetry. However, local environmental regulation and negative media coverage could reduce this information asymmetry, making greenwashing easier to be identified. It is the first study to investigate greenwashing–CFP relationship from institutional environment perspective.